INVENTARISASI EMISI SUMBER BERGERAK DI JALAN (ON ROAD) KOTA DENPASAR - Christine Prita Purwanto (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2015)
The growth of population in Denpasar City followed by increasing of transportation facilities that potentially cause pollution by vehicle emissions and cause serious environmental problems and which has adverse effect to the human health. The research aimed to estimate the number and distribution of emission gases on air pollutants, such as: PM10, NOx, SO2, CO, CO2 and HC. The calculation of estimated based on road mobile sources (On Road) in Denpasar City, includes all known sources such as the highway, small roads, terminals, and parking lots. The calculation of emissions is calculated by using the approach of emission estimation method. The total load of emissions by moving source on the street in Denpasar for each pollutant gases are: value of NOx is 3765.89 tons/year , value of SO2 is 212.34 tons/year, value of HC is 20049.87 tons/year, value of PM10 is 444.16 tons/year, value of CO2 is 984,280.21 tons/ year, and value of CO is 55432.04 tons/year. Overall, the total load of pollutant emissions gases of Denpasar City is greater than the total load of pollutant emissions gases in Palembang city. Spatially, the distribution of pollutant gas emissions are not spread evenly. The pollutants emissions of NOx, CO2, and HC for each gases have the highest values are about 115 – 239 tons/year, 26.944 – 4.735 tons/year, and 471 – 954 tons/year distributed at West Denpasar District and Niti Mandala Renon area. The highest pollutans emission of SO2 is about 15,5-44 tons/year, distributed at West Denpasar District. The highest pollutans emission of PM10 is about 11,5-21 tons/year, distributed at West Denpasar District, Badung Market area, Puputan Square area, and Niti Mandala Renon area. The highest CO pollutant emission is about 1277-1912 tons/year, distributed at West Denpasar District, Badung Market area, Puputan Square area, Niti Mandala Renon area, and Udayana University area.